Performance of Angora rabbits on various vegetable proteins incorporated diets - BHATT, R S (The Indian Journal of Animal Sciences, 2014)
An experiment was conducted on 45 German Angora for 225 days. Experimental diets (S) were prepared by using soyaflakes (T1), sunflower-cake (T2), mustard-cake (T4) as a source of protein. Lysine and methionine were supplemented @ 100g / q in sunflower-cake (T3) and mustard- cake (T5) based diets. The level of rice - phak was added to adjust equal level offibre in all the diets. The fibre fraction except ADF and cellulose was lowered in the sunflower-cake and mustardcake added diets. The body weight decreased (P<0.05) with amino acid supplementation in sunflower-cake based diet (T3) during second and third shearing. The highest gain in weight (2198g) was recorded in sunflower-cake based diet (T2). Pooled dry matter intake / head / day was highest in sunflower-cake based diet and was significantly (P <0.05) higher than other groups. Nonsignificant differences were recorded for total wool yield in different groups, however, the wool yield was highest (24S.7g) in T1 followed by T2 and TS (241.4g each). Digestibility of all the nutrients was significantly (P <0.05) affected with the incorporation oftest materials. Balance of nitrogen was depressed by sunflowercake and mustard-cake, which was improved by amino acid supplementation. From this experiment it was concluded that sunflower-cake and mustard- cake can replace soyaflakes in rabbit diet when included on equal nitrogen basis, however, lysine and methionine supplementation showed no beneficial effect on woolÂ production in Angora rabbits.